Confusion and Chinese character learning. Issue 1 (2nd January 2023) - Hong, Jon-Chao; Lin, Chien-hung; Tsai, Ya-hsun; Tai, Kai-Hsin
ABSTRACT: This study explores the relationship between the experience of confusion and the outcomes of Chinese character learning by learners of Chinese as a heritage language (CHL). Based on the claim that impasses triggering confusion can lead to deeper learning of conceptually difficult material, the study employed three impasse-driven tasks. The tasks were designed to trigger a state of cognitive disequilibrium in the participants. After first encountering the tasks in Session 1, the 117 CHL learners were given 1 week to resolve their impasse-driven tasks in their own time for 30 min (limited by the computer system). Afterwards, we announced the correct answer for them to look at for 3 days, and then Session 2 was administered 1 week after the feedback. The results of this study showed considerable improvement in differentiating near-homographs and homophones presented in a sentence, and correcting wrong Chinese characters. The study's results suggest that incorporating well-designed confusing content into Chinese learning may help CHL learners deepen their learning of Chinese characters.